Expert writers' descriptions and justifications of research instruments and materials: Using communicative resources to generate promotional effects. Issue 2 (2nd October 2017) - Lim, Jason
Abstract : The Methods section often serves as the driving force in the construction of empirical research reports. In research writing in particular, novice writers often overlook the importance of promotional elements that describe and justify the use of their research materials and instruments. In the present study, a discourse-analytic genre-based approach was used to study the information elements in a corpus of 32 experimental research reports published in eight established journals on language education. The related descriptions require the use of imperative clauses, verb phrases indicating obligations and functions, predicator-adverbial structures highlighting degrees of commonality and noun phrases denoting circumstances. Justifications of the use of research materials and instruments recurrently involve (1) structures that demonstrate writers' cognizance of difficulty levels, (2) means adjuncts indicating consistency, (3) integral citations in participial clauses and (4) cogent statements associating recent endorsements sought from multiple specialist informants in an academic community. The findings obtained can be used by instructors to demonstrate how contextual knowledge and communicative resources are generally used by expert writers to persuasively construct methodological knowledge.